THE IMAGE OF WOMEN IN THE FAIRY TALE OF THE KING AND PRINCESS OF THE FRAGRANT FLOWER LAKE BY AHMAD IJAZI H - Sherrin Salsabila; Erni (SOSIOEDUKASI, 2026)
This study aims to describe the image of women in the fairy  tale of Lake Raja and Putri Bunga Harum by Ahmad Ijazi H. This study is motivated by the importance of understanding the representation of women in children's literature and folklore as a medium that helps shape people's views on women. The research uses a qualitative approach with a content analysis method. The source of research data is in the form of the fairy tale text  of Danau Raja and Putri Bunga Harum by Ahmad Ijazi H., while the research data is in the form of narratives and dialogues that contain images of women. Data analysis was carried out through intensive reading, identifying data, classifying data based on women's image categories, interpreting the meaning of data, and drawing conclusions. This research uses Sugihastuti's theory of women's image which divides women's image into self-image and social image. The validity of the data is carried out through theoretical triangulation by comparing the findings of the research with the concepts of feminist literary criticism and relevant previous research. The results of the study showed that there were 31 data that represented the image of women. The data consisted of 21 self-image data and 10 social image data. Self-image includes physical image and psychic image. The physical image is displayed through the depiction of beauty, elegance, body health, and the specialties of the figure of Princess Bunga Harum who is depicted as having the fragrant scent of flowers. Psychic image is shown through intelligence, politeness, gentleness, compassion, loyalty, courage, and having determination in fighting for his desires. The social image of women is represented through the role of women in the family and society, such as maternal roles, social concern, respect for women, and the position of women as an important part of the kingdom's social structure. The findings of the study show that psychic imagery is the most dominant image so that women in fairy tales are not only represented through physical aspects, but also through personality qualities and social roles that they have.